2005
DOI: 10.1103/physrevd.71.123001
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on the redshift dependence of the dark energy potential

Abstract: We develop a formalism to characterize the redshift evolution of the dark energy potential. Our formalism makes use of quantities similar to the Horizon-flow parameters in inflation and is general enough that can deal with multiscalar quintessence scenarios, exotic matter components, and higher order curvature corrections to General Relativity. We show how the shape of the dark energy potential can be recovered non parametrically using this formalism and we present approximations analogous to the ones relevant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
1,402
1
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,168 publications
(1,434 citation statements)
references
References 48 publications
25
1,402
1
6
Order By: Relevance
“…We re-analyzed our data estimating the Hubble parameter from the upper envelope of the D4000 n − z relation. This approach has been already applied in the literature [12,82], and probing only the oldest galaxy population at each redshift it should provide an estimate of H(z) as close as possible to the unbiased one. We have considered the following mass ranges: log(M/M ⊙ ) > 11.25 for SDSS MGS, 11.65 < log(M/M ⊙ ) < 11.9 for LRGs, and log(M/M ⊙ ) > 10.6 for z > 0.4; these mass ranges are defined so that there is no strong median mass evolution in each subsamples along the spanned redshift range.…”
Section: A1 Estimating the Effect Of The Progenitor-bias On H(z)mentioning
confidence: 99%
See 2 more Smart Citations
“…We re-analyzed our data estimating the Hubble parameter from the upper envelope of the D4000 n − z relation. This approach has been already applied in the literature [12,82], and probing only the oldest galaxy population at each redshift it should provide an estimate of H(z) as close as possible to the unbiased one. We have considered the following mass ranges: log(M/M ⊙ ) > 11.25 for SDSS MGS, 11.65 < log(M/M ⊙ ) < 11.9 for LRGs, and log(M/M ⊙ ) > 10.6 for z > 0.4; these mass ranges are defined so that there is no strong median mass evolution in each subsamples along the spanned redshift range.…”
Section: A1 Estimating the Effect Of The Progenitor-bias On H(z)mentioning
confidence: 99%
“…Compared to other approaches based on the global spectral or photometric analysis [11,12,[18][19][20][21], it has been found that one of the most direct and solid ways of doing this is to use the 4000Å break (hereafter D4000) in ETG spectra, thanks to its linear dependence on age for old stellar populations [7]. This break is a discontinuity of the spectral continuum around λ rest = 4000Å due to metal absorption lines whose amplitude correlates linearly with the age and metal abundance (metallicity, Z) of the stellar population (in some age and metallicity ranges), that is weakly dependent (for old passive stellar populations) on star formation history (SF H), and basically not affected by dust reddening [7,[22][23][24] (see also Sect.…”
Section: Contents 1 Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We use the following datasets: a) observations of type Ia supernovae from the Joint Lightcurve Analysis (JLA) of the Sloan Digital Sky Survey (SDSS-II) and the Supernova Legacy Survey (SNLS) samples [12]; b) observations of baryon acoustic oscillations in the SDSS DR7 [13] and SDSS DR9 [14], in the WiggleZ Survey [15] and in the 6dF Galaxy Survey (6dFGRS) [16]; c) measurements of cosmic microwave background temperature anisotropy from 2015 Planck [17] and WMAP9-year [18]; d) observations of the Hubble rate H(z) from [19][20][21][22][23][24]. In the following subsections, the statistical analysis used to deal with those observables is briefly described.…”
Section: Observational Datamentioning
confidence: 99%
“…[15] it was used the recently published Hubble function H(z) data [Simon, Verde and Jimenez (SVJ)] [16], extracted from differential ages of passively evolving galaxies. This is interesting for, among other reasons, the function is not integrated over, in contrast to standard candle luminosity distances or standard ruler angular diameter distances.…”
Section: Observational Constraintsmentioning
confidence: 99%